PENYIDIKAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA GOLONGAN I JENIS SABU DIWILAYAH HUKUM POLRES SOLOK SELATAN (Studi No Lp/172/A/XII/2022/SPKT) - Lili Sundari, Nurlinda yenti dan (Normative Jurnal Ilmiah Hukum, 2025)
Narcotics are a type of drug/substance used in the world of medicine, but if used without restrictions and careful supervision, it can cause dependence and endanger health to the point of destroying the user's soul. The implementation of the investigation into drug abuse carried out by the South Solok Police Investigators did not run smoothly and experienced several obstacles. The problems discussed. The approach used is a descriptive sociological juridical approach that presents data in accordance with the facts systematically and logically according to the research objectives. The results of the study can be concluded with the following problems:1. There is a report from the community and witnesses are examined, then the suspect is arrested and after sufficient evidence is obtained and the suspect is detained and evidence is confiscated, and the suspect is examined and a report is made and handed over to the public prosecutor. 2. The obstacles faced by investigators are the occurrence of mistaken arrests of suspects, lack of facilities and infrastructure, Suspects are difficult to find because suspects make transactions by moving from place to place, making it difficult for investigators to find suspects. 3. Efforts to overcome obstacles in the investigation are that investigators must be more observant and careful in the arrest process so that there is no mistake in mistakenly arresting suspects with other members of the public, The second way is that the South Solok Police must improve the facilities and infrastructure to conduct investigations, and in overcoming the lack of facilities used by investigators to find other ways, namely by using local community vehicles to continue the arrest, and to overcome the occurrence of mistaken arrests of suspects, namely by dividing groups and scattering in the search for the suspect.